Resource Assessment of Wind Energy Potential of Mokha in Yemen with Weibull Speed - El-Bshah, Abdulbaset; Al-Wesabi, Fahd N.; Al-Kustoban, Ameen M.; Alamgeer, Mohammad; Nemri, Nadhem; Eltahir, Majdy M.; Mahgoub, Hany; Negm, Noha (Tech Science Press, 2021)
The increasing use of fossil fuels has a significant impact on the environment and ecosystem, which increases the rate of pollution. Given the high potential of renewable energy sources in Yemen and other Arabic countries, and the absence of similar studies in the region. This study aims to examine the potential of wind energy in Mokha region. This was done by analyzing and evaluating wind properties, determining available energy density, calculating wind energy extracted at different altitudes, and then computing the capacity factor for a few wind turbines and determining the best. Weibull speed was verified as the closest to the average actual wind speed using the cube root, as this was verified using 3 criteria for performance analysis methods (R2= 0.9984, RMSE= 0.0632, COE= 1.028). The wind rose scheme was used to determine the appropriate direction for directing the wind turbines, the southerly direction was appropriate, as the winds blow from this direction for 227 days per year, and the average southerly wind velocity is 5.27 m/s at an altitude of 3 m. The turbine selected in this study has a tower height of 100m and a rated power of 3.45 MW. The capacitance factor was calculated for the three classes of wind turbines classified by the International Electrotechnical Commission (IEC) and compared, and the turbine of the first class was approved, and it is suitable for the study site, as it resists storms more than others. The daily and annual capacity of a single, first-class turbine has been assessed to meet the needs of 1,447 housing units in Mokha region.